Evolutionary music - Yong, Deborah Ee San. (2009)
Evolutionary Music is one of the more recent areas in the Evolutionary Computation domain where music is created, arranged or improvised using computers. The goal in evolutionary music research is to create an intelligent system which produces aesthetically pleasing music to the user based the application of evolutionary algorithms such as genetic algorithms and some form of music structure representation.